Resignifying Interculturality in the Costa Rican Educational System - Salazar Chavarría, Kenett (2023)
Taking critical-decolonial thinking as a reference, a theoretical review is made of the curricular policies in Intercultural Education developed in Costa Rica during the last decades; with the objective of problematizing the methods selected for their design and execution, while opening a theoretical debate from the teachers' collective around the hegemonic character of the contents that the Official Curriculum intends to transmit. In line with the proposed objectives, this theoretical essay is based on the technique of content analysis, to demonstrate that the curricular reforms in interculturality are framed within the neoliberal globalization project, whose purpose is the reproduction of historical domination logics, in this case through the official educational systems, under the guise of discourses such as tolerance and inclusion. In view of these scenarios, emphasis is placed on the need to vindicate the role of teachers in the construction of collective proposals that respond to the diversities present in the country's educational communities.